2020
DOI: 10.3390/en13184866
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multiple Anaerobic Co-Digestions and Related Microbial Community of Molasses with Rice-Alcohol Wastewater

Abstract: Molasses is a highly dense and refined byproduct produced in the sugarcane industry, and it contains high amounts of degradable compounds. Through bioconversion, these compounds can be transformed into renewable products. However, the involved biological process is negatively influenced by the high chemical oxygen demand (COD) of molasses and ion concentration. The co-digestion of molasses with rice-alcohol wastewater (RAW) was compared with its mono-digestion at an increasing organic loading rate (OLR). Both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The main purpose of adding rice alcohol wastewater with molasses was to stabilize the process. In addition, Khan et al (2020) confirmed that the RAW could be a good co-substrate for stable anaerobic digestion of molasses [22]. As a result, the COD removal rate at day 45 increased in control was (86.74 ± 0.41%), R1 (87.65%), R2 (87.65%), R3 (87.77%), and R4 (87.71%) (Figure 1).…”
Section: Effects Of Different Concentration Of Nickel (Ni) On Cod Removal Ratementioning
confidence: 61%
See 4 more Smart Citations
“…The main purpose of adding rice alcohol wastewater with molasses was to stabilize the process. In addition, Khan et al (2020) confirmed that the RAW could be a good co-substrate for stable anaerobic digestion of molasses [22]. As a result, the COD removal rate at day 45 increased in control was (86.74 ± 0.41%), R1 (87.65%), R2 (87.65%), R3 (87.77%), and R4 (87.71%) (Figure 1).…”
Section: Effects Of Different Concentration Of Nickel (Ni) On Cod Removal Ratementioning
confidence: 61%
“…The inoculum sludge was taken from the last experiment conducted on anaerobic co-digestion of molasses and rice alcohol wastewater [22]. Molasses was taken from the Guangxi Guitang (Group) Co., Ltd. (Guigang, China).…”
Section: Inoculum Sludge and Molassesmentioning
confidence: 99%
See 3 more Smart Citations